The cost of robotics: an analysis of the added costs of robotic-assisted versus laparoscopic surgery using the National Inpatient Sample - Khorgami, Zhamak; Li, Wei T.; Jackson, Theresa N.; Howard, C. Anthony; Sclabas, Guido M. (Surgical endoscopy, 2019)
Background Robotic-assisted surgery (RAS) with its advantages continues to gain popularity among surgeons. This study analyzed the increased costs of RAS in common surgical procedures using the National Inpatient Sample. Methods Retrospective analysis of the 2012–2014 Healthcare Cost and Utilization Project-NIS was performed for the following laparoscopic/robotic procedures: cholecystectomy, ventral hernia repair, right and left hemicolectomy, sigmoidectomy, abdominoperineal resection, and total abdominal hysterectomy (TAH). Patients with additional concurrent procedures were excluded. Costs were compared between the laparoscopic procedures and their RAS counterparts. Total costs and charges for cholecystectomy (the most common procedure in the dataset) were compared based on the payer and characteristics of hospital (region, rural/urban, bed size, and ownership). Results A total of 91,630 surgeries (87,965 laparoscopic, 3665 robotic) were analyzed. The average cost for the laparoscopic group was $10,227 ± $4986 versus $12,340 ± $5880 for the robotic cases ( p < 0.001). The overall and percentage increases for laparoscopic versus robotic for each procedure were as follows: cholecystectomy $9618 versus $10,944 (14%), ventral hernia repair $10,739 versus $13,441 (25%), right colectomy $12,516 versus $15,027 (20%), left colectomy $14,157 versus $17,493 (24%), sigmoidectomy $13,504 versus $16,652 (23%), abdominoperineal resection $17,708 versus $19,605 (11%), and TAH $9368 versus $9923 (6%). Hysterectomy was the only procedure performed primarily using RAS and it was found to have the lowest increase in costs. Increased costs were associated with even higher increases in charges, especially in investor-owned private hospitals. Conclusion RAS is more costly when compared to conventional laparoscopic surgery. Additional costs may be lower in centers that perform a higher volume of RAS. Further analysis of long-term outcomes (including reoperations and readmissions) is needed to better compare the life-long treatment costs for both surgical approaches.